PEFR and FEF25-75 in Rheumatoid Arthritic Female and their Relationships with Duration of the Disease - Yesmin, Farzana; Begum, Shelina; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2011)
Background: Rheumatoid Arthritis (RA) is a chronic, progressive multisystemic inflammatory disorder of unknown etiology affecting approximately 1% of the population. Pulmonary involvement is a frequent extraarticular manifestation in rheumatoid arthritis. Objective: To observe PEFR, FEF25-75 in female patients of RA in order to find out their relationships with duration of the disease. Methods: This cross-sectional study was carried out in the Department of Physiology, BSMMU, Dhaka, between January and December 2009 on 90 RA female patients of 30-50 years age (Group B). For comparison, 30 age and BMI matched apparently healthy subjects (Group A) were also studied. According to the duration of disease, RA patients were subdivided into B1 (newly diagnosed), B2 (3-5 years) and B3 (6- 10 years). They were selected from the Out Patient Department of Physical Medicine of Bangabandhu Sheikh Mujib Medical University, Dhaka. PEFR, FEF25-75 of all the subjects were measured by a digital MicroDL spirometer. Results were expressed as percentage of predicted value. For statistical analysis One-Way ANOVA, Unpaired Student's 't' test and Pearson's correlation coefficient test were performed. Results: The mean percentage of predicted values of these lung function parameters in the healthy female subjects and newly diagnosed (B1) RA patients were within normal ranges. The mean percentage of predicted values of both the spirometric variables were significantly lower in B3 compared to those in B2 (PEFR p<0.001, FEF25-75 p<0.001), B1 (PEFR p<0.05, FEF25-75 p<0.02) and A (PEFR p<0.05, FEF25-75 p<0.01). Again the same parameters were significantly lower in B2 in comparison to those of B1 (PEFR p<0.001, FEF25-75 p<0.05) and A (PEFR p<0.001, FEF25-75 p<0.05). In addition both the ventilatory variables had significant (p<0.001) negative correlation with durations of disease. Conclusion: This study reveals that pulmonary functions may be lower in patients with RA and their lung function is inversely related to the duration of disease. Key Words: PEFR; FEF25-75; Rheumatoid Arthritis DOI: http://dx.doi.org/10.3329/jbsp.v6i1.8086 J Bangladesh Soc Physiol. 2011 June; 6(1): 58-63